Characteristics and Prognosis of Hepatocellular Carcinoma in Japanese Patients Undergoing Dialysis. Issue 5 (7th September 2017) - Toyoda, Hidenori; Hiraoka, Atsushi; Tada, Toshifumi; Michitaka, Kojiro; Takaguchi, Koichi; Tsuji, Kunihiko; Itobayashi, Ei; Takizawa, Daichi; Hirooka, Masashi; Koizumi, Yohei; Ochi, Hironori; Joko, Koji; et al.
Abstract: Patients with end‐stage renal disease who are undergoing dialysis may be at high risk of developing hepatocellular carcinoma (HCC). We investigated the characteristics and prognosis of HCC in patients undergoing dialysis in Japan. Patients characteristics, progression of HCC at diagnosis, and survival rates after diagnosis were compared between 108 HCC patients undergoing dialysis and 526 non‐dialysis patients followed up at liver center. The comparisons were also performed after adjusting for patient age, gender, platelet count, and etiology using propensity‐score matching. HCC was more advanced in patients undergoing dialysis than in non‐dialysis controls. The 3‐ and 5‐year survival rates of patients undergoing dialysis were 56.3% and 38.3%, respectively, which were lower than those of non‐dialysis controls (66.5% and 52.7%, respectively, P =  0.0026). The results were the same after propensity score matching ( P =  0.0014). In Japan, HCC was more advanced at diagnosis in patients undergoing dialysis in comparison to HCC in patients at liver centers, resulting in a lower survival rate after diagnosis.